A new tool for conjunction analysis of ISRO's operational satellites, Close Approach Prediction Software: CLAPS. Issue 3 (September 2020) - Singh, Satyendra
Abstract: During the lifetime of an operational spacecraft, a situation may occur when it faces a close approach with other orbiting space objects. The mitigation strategy for minimizing threat from orbiting space objects is to first carry out proximity analysis for operational spacecraft's (primary) with all other catalogued orbiting space objects (secondary). In case of a possible close approach, to plan an evasive collision avoidance maneuver. The ever-increasing number of space objects around the Earth demands this kind of analysis on daily basis by satellite operators. Presently, ISRO is operating close to 50 satellites in LEO and GEO/GSO orbits and this number is increasing each year at a rapid rate. At present the NORAD TLE catalogue consists of more than 18000 unclassified space objects. The large number of object pairs require enormous amount of computational load to do such kind of analysis on daily basis. Therefore, an efficient and user-friendly tool to predict the future close approaches is necessary for satellite operators. In this paper, methodology is designed and developed for carrying out conjunction analysis for all operational satellites with catalogued space objects. In the design, efficient approach is adopted to reduce the computation time. Each object pair goes through screening process using pre-filters like perigee-apogee test and smart sieves. These filters are based on basic flight dynamics rules. Only those pairs which are passed by all filters are subjected to relative distance function method for finer assessment. For the candidate pairs which violate the specified minimum Inter-Satellite-Distance (ISD) limit, collision probability is computed. For operational satellites, latest available orbit determination results at control centre are used and orbit propagation is done with high fidelity ephemeris model. Orbit propagation of catalogued objects with TLE is done using SGP4 model. Using this design methodology, Close Approach Prediction Software (CLAPS) is developed in C++ language, to predict the future close approaches for multiple operational satellites with complete TLE catalogue in single run. CLAPS s/w is tested for various close encounter cases and results are validated with STK's AdvCAT tool. The close approach time and minimum distance are found to match up to millisecond and millimetre level respectively. The results of few actual close approach scenarios are presented and discussed. CLAPS is being used regularly at ISRO's Master Control Facility, Hassan for routine monitoring of close approaches.